Security risk analysis used by Kuwait government sectors - Al-Enezi , Khalid Abdulkareem; Alshaikhli, Imad Fakhri Taha; Alhatem, Khaled; Al-kandari, Abdulrahman (2014)
Permanent use of computer in our daily lives has to be protect our personal information from any external threat, if cyber security is the solution to build a safe space greeting mail in government agencies. Risk analysis is an essential process in risk management, There is two kinds of the risk qualitative and quantitative. Survey was distributed to government entities in Kuwait to prove the main risk and how to secure the risk analysis, and business continuity plan. Was distributed to the employees who work in these sections in the government entities. and 90 replies, 74% of them are not penetrate their organization before - 69% of government agencies change the password automatically - 58% have a team to analyze security risks. To resolve the problem business continuity plan that cover and satisfies the requirements of all government entities in Kuwait, according to theoretical and statistical studies, hence ensuring the continuity of all e-services developed in Kuwait as part of the government project, provide a special budget to protect the security of information in all governmental entity. Inform the relevant staff of all that is new and all the developments in the field of information security. Increase educational programs flags on the importance of the security information.